Biopsy of the sentinel lymph node in oral squamous cell carcinoma: analysis of error in 100 consecutive cases. Issue 7 (September 2018) - Holden, A.M.; Sharma, D.; Schilling, C.; Gnanasegaran, G.; Odell, E.W.; Sassoon, I.; McGurk, M.
Abstract: UK national guidelines in 2016 recommended that sentinel lymph node biopsy should be offered to patients with early oral cancer (T1-T2 N0) in which the primary site can be reconstructed directly. This study describes the pitfalls that can be avoided in the technique of biopsy to improve outcomes. We retrospectively analysed the data from 100 consecutive patients and recorded any adverse events. Lymphatic drainage of tracer failed in two patients as a result of procedural errors. Two patients with invaded nodes developed recurrence after total neck dissection, one after micrometastases had been diagnosed, and the other as a result of extranodal spread that had led to understaging and therefore undertreatment. Two results would not have been mistakenly classified as clear if all the harvested nodes had been analysed histologically according to the protocol. The disease-specific (96%) and disease-free (92%) survival were better than expected for a group of whom a third had stage 3 disease. If all harvested nodes had been analysed by the correct protocol then two of the three nodes wrongly designated clear would have been detected, two deaths potentially avoided, and the false-negative rate would have fallen from 8.3% to 2.7%. We conclude that minor deviations from protocol can result in a detrimental outcome for the patient.